The Relation Of Sulphur To The Overpoling Of Copper- Discussion (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
F. JOHNSON,* Birmingham, England (written discussion t).--. Mr. Skowronski's first melting experiments tend to show that ingots with a "level set" may be obtained without oxygen. Now it is characteristic of all metals which occupy a smaller volume when solid than they do when molten to "pipe." In vertical-cast ingots, this pipe resembles a horn-shaped cavity, with the wide mouth uppermost. In horizontal-cast ingots, the pipe is a longitudinal furrow along the center-line of the ingot surface. If copper be successfully deoxidized and degasified, this furrow will inevitably be produced. In the author's oxygen-free ingots, it is. clear that gases were occluded and these gases effectively opposed the formation of a pipe or furrow by shrinkage (fluid contraction). It is riot a special property of any particular gas which produces this effect. Hence it is not surprising that the author has succeeded in producing level and overpoled ingots through the agency of sulphur. dioxide gas. That he has counteracted the overpoling influence of sulphur by means of oxygen is somewhat difficult to explain, since the well known reaction between cuprous sulphide and cuprous oxide should result in the production of sulphur dioxide gas. Why the presence of excess cuprous oxide should neutralize the overpoling influence of this gas without eliminating sulphur is not at all clear. It is to be regretted that the oxygen was not determined in the bars given in Tables 3 and 4. It is by no means established that sulphur is responsible for the over, poling of ingots given in Table 4, since carbon was used for overpoling. If, however, the same kind of poling treatment was given as that applied in the case of ingots in Table 1, the responsibility of sulphur assumes more definite shape. The author rightly points out that Mr. Johnson's theory of the equilibrium between gases and cuprous oxide does not explain why a simple addition of cuprous oxide does not correct an overpoled charge. Such a charge must be re-worked to "set" copper. This re-working (rabbling) undoubtedly forcibly removes the excess gases, which are not removable by cuprous oxide.